The Effect of Carbon Emission Disclosure on Company Value Using Corporate Governance as a Moderating Variable - Nona, Marietha Anggryani Dua; Putikadea, Insyirah (Majapahit Journal of Islamic Finance and Management, 2025)
This study aims to determine the effect of carbon emission disclosure and profitability on firm value with corporate governance as a moderating variable. The research method used is quantitative method, with SPSS software, and data analysis techniques using multiple linear regression analysis, and Moderated Regression Analysis (MRA). This study uses a sample of holding companies involved in the energy sector, and listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. The results show that carbon emission disclosure has a negative effect on firm value, and corporate governance is able to strengthen the relationship between carbon emission disclosure and firm value.